Metal-free and highly regioselective synthesis of N-heteroaryl substituted pyrazoles from α, β-unsaturated N-tosylhydrazones and heteroaryl chlorides. Issue 33 (15th August 2019) - Zeng, Lin; Guo, Xiao-Qiang; Yang, Zai-Jun; Gan, Ya; Chen, Lian-Mei; Kang, Tai-Ran
Graphical abstract: Highlights: A new reaction of N -tosylhydrazones with N -heteroaryl chlorides has been developed. The reaction provided bi(heteroaryl)s in excellent yield and regioselectivity. The procedure is operationally simple and applicable for the large-scale synthesis. Abstract: A cascade cyclization/nucleophilic aromatic substitution (SN Ar) reaction of α, β-unsaturated N -tosylhydrazones with N -heteroaryl chlorides was developed for the synthesis of N -heteroaryl pyrazole derivatives. This one-pot reaction provided bi(heteroaryl) derivatives in good to excellent yields and with excellent regioselectivity. The procedure is operationally simple and applicable to large-scale synthesis.